Secret selves : confession and same-sex desire in Victorian autobiography - Buckton, Oliver S. (Chapel Hill : University of North Carolina Press, 1998)
Focusing on the representation of same-sex desire in Victorian autobiographical writing, Oliver Buckton offers significant new readings of works by such influential 19th-century writers as Edward Carpenter, John Henry Newman, John Addington Symonds, and, in an epilogue, E.M. Forster, and reveals the "confessional" elements of their writings.
Introduction: The Self and Its Secrets -- Ch. 1. An Unnatural State: Secrecy and "Perversion" in John Henry Newman's Apologia pro Vita Sua -- Ch. 2. The Secret Which I Carried: Desire and Displacement in John Addington Symonds's Memoirs -- Ch. 3. Defacing Oscar Wilde -- Ch. 4. A Double Nature: The Hidden Agenda of Edward Carpenter's My Days and Dreams -- Epilogue: Strange Desires: Sexual Reconstruction in E.M. Forster's Secret Fictions.
Includes bibliographical references (pages 251-259) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Englisch, ...; English prose literature -- 19th century -- History and criticism; Autobiography; Male authors, English -- 19th century -- Biography -- History and criticism; Homosexuality and literature -- Great Britain -- History -- 19th century; Gay men -- Great Britain -- Biography -- History and criticism; Gay men's writings, English -- History and criticism; Great Britain -- History -- Victoria, 1837-1901 -- Historiography; Confession in literature; Desire in literature; Authors, English -- 19th century -- Biography -- History and criticism; Homosexuality and literature -- England -- History -- 19th century; Gay men -- England -- Biography -- History and criticism; Autobiographies as Topic; Prose anglaise -- 19e siècle -- Histoire et critique; Autobiographie; Écrivains anglais -- 19e siècle -- Biographies -- Histoire et critique; Homosexualité et littérature -- Angleterre -- Histoire -- 19e siècle.; Homosexuels masculins -- Angleterre -- Biographies -- Histoire et critique; Écrits d'homosexuels anglais -- Histoire et critique; Confession dans la littérature.; Désir dans la littérature.; Grande-Bretagne -- Histoire -- 1837-1901 (Vic.) -- Historiographie; Homosexualité et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Homosexuels masculins -- Grande-Bretagne -- Biographies -- Histoire et critique; Grande-Bretagne -- Histoire -- 1837-1901 (Victoria) -- Historiographie; autobiography (genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Gay & Lesbian; Gay men; Autobiography; Confession in literature; Desire in literature; English prose literature; Gay men -- Biography; Gay men's writings, English; Historiography; Homosexuality and literature; Male authors, English -- Biography; England; Great Britain; Authors, English -- Biography; Autobiografieën.; Engels; Homoseksuelen; Bekentenis; Wensen; Autobiografie; Homosexualität; Schriftsteller; Großbritannien; Geschichte 1845-1960.; Englisch; 1800-1901; Autobiography; Autobiographies; Criticism, interpretation, etc; History; autobiographies (literary works); Autobiographies